Knowledge as cause and tool for resistance against large scale mining: heuristic cases in Ecuador - Cristina Espinosa (Íconos)
This article argues that production of knowledge has become a key practice in processes of resistance and opposition to large scale mining projects. The point of departure is the observation that that- beyond mere resistance- socio-environmental conflicts regarding the extraction of minerals, include the production and circulation of knowledge. Opponents to large scale mining projects use knowledge in their efforts to influence political decisions regarding natural resources, territories and people. Not every kind of knowledge is recognized as equally legitimate or is evenly distributed among participants in the course of these struggles. Questions can be posed about the roots of these epistemic asymmetries and about how they relate to wider conflicts regarding domination, dispossession and control. These questions are illuminated using the theoretical contributions provided by approaches such as the sociology of knowledge, Latin American de-colonial thought, and feminist contributions to the study of science, technology and society. Taking these relatively novel epistemic approaches as a point of departure, three heuristic cases in Ecuador are analyzed: Intag, Azuay and Cordillera del Condor. These cases show that the production of contestatory knowledge is an important resource in efforts to counteract the socio-environmental impact of the opening of new areas no large scale mining.